New labour rights indicators: Method and trends for 2000–15. (11th September 2019) - KUCERA, David; SARI, Dora
Abstract: This article describes a new method for constructing indicators of freedom of association and collective bargaining (FACB) rights based on the coding of violations in nine textual sources, including six from the ILO, and texts from national legislation. The indicators were constructed for 185 ILO member States for five years between 2000 and 2015 and launched in 2015 by the Center for Global Workers' Rights at Penn State University, together with the Global Labour University. Following a Resolution by the International Conference of Labour Statisticians in October 2018, the method provides the basis for Sustainable Development Goal indicator 8.8.2 on labour rights.